THE MODEL OF HYPOCHONDRIAC DISORDER PREVENTION FOR ITS IMPLEMENTATION INTO THE EDUCATIONAL PROCESS IN THE ASPECTS OF THE INNOVATIVE APPROACHES - Vysnyuk, Inessa (PSYCHOLOGICAL JOURNAL, 2019)
The article examines the formation of professional readiness to self-realization of future specialists having hypochondriac nosology with psychosomatic traits through the prism of the competency-based tasks. The criterion-resultant component of the model is determined, which includes motivational-value, cognitive-personal, creative-activity, reflexivity-regulatory criteria of increase of future specialists’ readiness to psychological-emotional safety of activities. The model of this type is efficient due to the fact that, to identify the essence of any object, it is necessary to determine its basic location, which is ensured by the unity and mutual influence of its structural and functional components. The model reflects the goals, the treatment and prevention of hypochondriac disorder origin and development, the method of its implementation is aimed to achievement positive dynamics in psychological competence formation for people with hypochondriac disorders. Within the innovative approach, a system of measures for hypochondria prevention in accordance with the established psychological-diagnostic criteria was introduced into the educational process. The above-mentioned criteria contributed to the identification of hypochondria psychological and temporal indicators, serving as a methodological basis for development and practical implementation of the system of chrono-psychological prediction of the hypochondria course, which have help us outline the specific medical and psychological rehabilitation of specialists in various occupations with hypochondriac disorders. The algorithm for chrono-biological forecast of psychological symptoms, the disorder course, the treatment effectiveness and adaptive capability optimization for patients with hypochondriac disorders is presented. The research participants were informed on hypochondria relapses, the causes of its recurrence and consequences. The determined criteria and indicators help to emphasize the importance of professional self-realization of patients with hypochondriac disorders and provide an opportunity to perform initial diagnosis of the investigated quality; to substantiate the psychological conditions for this quality formation and to perform a final diagnostic study in order to determine the experiment efficiency.